2020
DOI: 10.14744/less.2020.25901
|View full text |Cite
|
Sign up to set email alerts
|

Complications during laparoscopic cholecystectomy performed due to acute cholecystitis

Abstract: Introduction: Today, laparoscopic cholecystectomy is essential in the treatment of acute cholecystitis, particularly in all patients who have applied in the early period and can tolerate surgery. Although the rates of complication and conversion to open surgery tend to decrease over time with the increasing experience, they are still among the important problems today. The most important complications of laparoscopic cholecystectomy in acute cholecystitis are biliary tract injuries and bleeding. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…Emergency patients had significantly higher Nassar grades compared to patients undergoing elective surgery. While no studies comparing Nassar grade levels based on the type of surgical indication for cholecystectomy were found, previous research indicated a potential connection between complications during laparoscopic cholecystectomy and variations in C-reactive protein (CRP) levels, with notable discrepancies in CRP values and conversion criteria across different studies1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . While our study did not specifically investigate the relationship between CRP levels and conversion, this aspect warrants attention in future research to understand better how CRP may be linked to the Nassar scale.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency patients had significantly higher Nassar grades compared to patients undergoing elective surgery. While no studies comparing Nassar grade levels based on the type of surgical indication for cholecystectomy were found, previous research indicated a potential connection between complications during laparoscopic cholecystectomy and variations in C-reactive protein (CRP) levels, with notable discrepancies in CRP values and conversion criteria across different studies1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . While our study did not specifically investigate the relationship between CRP levels and conversion, this aspect warrants attention in future research to understand better how CRP may be linked to the Nassar scale.…”
Section: Discussionmentioning
confidence: 99%